Enhancing Business Performance with Market Information Tools - Nanda Adi Prianggara; Raihan Maulana Yusuf; Atthariq Binar Satriya; Husna Taufiqurrohman; Andriyas Ardian Saputra (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
Market information tools play an increasingly vital role in shaping business strategies and enhancing performance in competitive environments. This article reviews recent literature and practical implementations of digital tools such as Customer Relationship Management (CRM), market intelligence systems, analytics dashboards, and AI-driven insights to empower strategic decisions. The review adopts a descriptive qualitative method based on literature from the last five years. Findings show that businesses equipped with integrated market information tools can respond faster to trends, identify customer needs more accurately, and allocate resources more efficiently. The article provides recommendations for adopting these tools to achieve sustainable growth.